Overview of the First International Meeting on Rapid Responses to Steroid Hormones - Norman, Anthony W.; Wehling, Martin (Steroids, 1999)
It is now evident that all the actions of estrogen and progesterone cannot be attributed to their classic receptors. These unattributed actions are referred to as nonclassical or membrane-initiated actions. Some of the membrane-initiated actions are mediated by the classical steroid receptors or their splice variants that localize to the plasma membrane. There are also nonclassical steroid receptors that do not share any structural features with the classical steroid receptors. Therefore, a synopsis of the structure, mechanism of action and physiological role that each nonclassical receptor for estrogen and progesterone plays in regulating of female reproduction will be presented in this article. - The steroid hormone 1α,25-dihydroxyvitamin D3 [1α,25(OH)2D3] produces biological responses by interaction with both a well-characterized nuclear receptor (VDRnuc) to regulate gene transcription and with an as-yet uncharacterized membrane-associated protein/receptor (VDRmem) to generate a variety of rapid, non-genotropic responses. We report for the first time that [3H]<mtext>[</mtext>3<mtext>H</mtext><mtext>]</mtext>1α,25(OH)2D3 binds with high affinity to a chick duodenal caveolae-enriched membrane fraction (CMF) isolated without the use of detergents. Caveolae are plasma membrane invaginations implicated in signal transduction and molecular transport processes. Using the CMF fraction as a possible source of VDRmem, we found that the in vitro binding of [3H]<mtext>[</mtext>3<mtext>H</mtext><mtext>]</mtext>1α,25(OH)2D3 was ligand dependent and saturable; the KD and Bmax were 1.3±0.6 nM and 29±11 fmol 1,25(OH)2D3/mg protein (n=17), respectively. Immunoblot analysis of the CMF confirms the presence of caveolin-1, a marker protein for membranes with caveolae. Therefore, chick CMF may represent a good source for isolation and characterization of the putative VDRmem for 1α,25(OH)2D3. - Evidence shows that environmental compounds can interfere with the endocrine systems of wildlife and humans. The main sink of such substances, called endocrine disruptors (EDs), which are mainly of anthropogenic origin, is surface water; thus, aquatic vertebrates such as fishes and amphibians are most endangered. Despite numerous reports on EDs in fishes, information about EDs in amphibians is scarce, and this paucity of information is of particular concern in view of the worldwide decline of amphibians. EDs could contribute to changes of amphibian populations via adverse effects on reproduction and the thyroid system. In amphibians, EDs can affect reproduction by (anti)estrogenic and (anti)androgenic modes of action that produce severe effects including abnormal sexual differentiation. ED actions on the thyroid system cause acceleration or retardation of metamorphosis, which may also affect population levels. Our broad knowledge of amphibian biology and endocrinology indicates that amphibians are very suitable models for the study of EDs. In particular, effects of EDs on the thyroid system triggering metamorphosis can be determined easily and most sensitively in amphibians compared to other vertebrates. A new classification of EDs according to their biological modes of action is proposed because EDs have quite heterogeneous chemical structures, which do not allow prediction of their biological effects. Methods and strategies are proposed for identification and risk assessment of EDs, whether as pure test substances or as mixtures from environmental samples. Effects of EDs on the thyroid system of amphibians can be assessed by a single animal model (Xenopus laevis), whereas the various types of reproduction need comparative studies to investigate whether general endocrine principles do exist among several species of anurans and urodeles. Thus, at least one anuran and one urodelean model are needed to determine ED interference with reproduction. - The aim of this study was to examine the state of anxiety and the 17β-estradiol and progesterone levels in rats tested in the elevated plus-maze during the four phases of the estrous cycle. Male rats, female rats during each of the four phases of the estrous cycle, ovariectomized rats, and diestrus female rats treated with estradiol were tested in the elevated plus-maze between 8:00 and 10:00 a.m. Blood was collected from all rats for the determination of 17β-estradiol and progesterone levels. Female rats in the proestrus group spent more time in the open arms than diestrus rats (P<.05). There were no significant differences in the percentage of entries into the open arms or in the number of entries into the closed arms among the phases of the estrous cycle or between males and normal or ovariectomized females. Serum estradiol levels were higher (P<.05) during proestrus compared to estrus, metestrus, and diestrus in control and plus-maze tested female rats, but there were no significant differences in progesterone levels. Treating diestrus female rats with estradiol to produce estradiol plasma concentrations similar to those seen during proestrus abolished the difference in the percentage of time spent in the open arms by proestrus and diestrus rats. Since the time spent in the open arms of the plus-maze is inversely related to anxiety, we conclude that the anxiety levels of female rats were lower in proestrus than during diestrus, and that the levels of estradiol modulate this response. - In the traditional theory of steroid action, steroids bind to intracellular receptors and modulate nuclear transcription after translocation of steroid-receptor complexes into the nucleus. Due to similarities of molecular structure, specific receptors for steroids, vitamin D3 derivatives, and thyroid hormone are considered to represent a superfamily of steroid receptors. While genomic steroid effects characterized by their delayed onset of action and their sensitivity to blockers of transcription and protein synthesis have been known for several decades, rapid actions of steroids have been more widely recognized and characterized in detail only recently. Rapid effects of steroids, thyroid hormones, and the steroid hormone metabolite of vitamin D3, 1α, 25-dihydroxyvitamin D3, on cellular signaling and function may be transmitted by specific membrane receptors. Binding sites in membranes have been characterized, exposing binding features compatible with an involvement in rapid steroid signaling. Characteristics of putative membrane receptors are completely distinct from intracellular steroid receptors, a fact which is further supported by the inability of classic steroid receptor antagonists to block nongenomic steroid actions. A putative progesterone membrane receptor has been cloned and functionally expressed with regard to progesterone binding. Development of drugs that specifically affect nongenomic action alone or even both modes of action may find applications in various, areas such as in the cardiovascular and central nervous systems and treatment of preterm labor, infertility, and electrolyte abnormalities.
Gesehen am 17.08.2022